(untitled) (Research, Society and Development, 2020)
The increase in obesity rates and the ineffectiveness of clinical treatment mean that surgical treatments’ search should be considered. Moreover, both anemias and nutritional deficiencies are common consequences of bariatric surgery. This study aims to explain the possible treatments that seek to minimize nutritional changes and how the theme has been addressed in different analyses. The search for articles was through the PubMed and Scientific Electronic Library Online (SciELO) databases using the terms "anemia and gastrectomy" and "anemia and Bariatric Surgery" and their correspondents in Portuguese. Inclusion criteria were considered: a) articles b) be available in full text c) studies available in Portuguese, English or Spanish d) clinical research e) to have been published between 2015 and 2020 f) articles that contemplate needful anemias and clinically significant consequences of bariatric surgery. Texts unrelated to the theme and duplicates were excluded. Thus, of the 22 articles presented by the search in the databases, 11 were selected by affinity to the search theme and 11 articles were excluded because they were not related to the subject. From this process, it was realized that anemias and nutritional deficiencies are a common consequence in post-gastrectomy patients. Thus, preoperative supplementation and post-surgical nutritional monitoring are interventions to avoid nutritional deficiencies. It is important to highlight the follow-up of patients gastrectomized by a multiprofessional team to ensure a better quality of life for the patient.